Globalization of American Interpretation Debate: Originalists, Living Constitutionalists, and the Drifters - Chowdhury, M Jashim Ali; Ahmed, Jubaer (The Asian Yearbook of Human Rights and Humanitarian Law)
The American Debate on originalism and living constitutionalism has travelled worldwide. This paper examines four Western and six South and Southeast Asian jurisdictions and argues that the modalities of the Debate there reflect their party systems, judicial appointment processes and the judiciaries’ institutional grandeur. While the non-politicised judiciaries of the West - such as the European courts and the German federal court - usually prefer the living constitutionalist approach, the politics-prone judiciaries, such as those in Australia and Canada, risk turning into US-styled battle grounds of originalism and living constitutionalism. In the South and Southeast Asian region, judiciaries working in party-dominant systems, such as Singapore and Hong Kong, prefer originalist interpretations. However, the courts in comparatively illiberal democracies, such as Malaysia, India, Bangladesh and Pakistan, adopt approaches that serve their social and institutional self-interests. It leads some to create a hotchpotch of originalism and living constitutionalism and others to drift aimlessly.